Clinician modifiable factors associated with better quality of life in children with acquired brain injury undergoing rehabilitation. (21st March 2018) - Connell, Tim; Paterson, Julia; Roberts, Rachel M.; Raghavendra, Parimala; Sawyer, Michael; Russo, Remo N.
ABSTRACT: Objectives : To identify clinician-modifiable factors related to quality of life (QOL) in children with acquired brain injury (ABI). Participants and methods : Thirty-nine children attending an ABI rehabilitation program (5–18 years) were assessed using the Personality Inventory for Children-2, Vineland Adaptive Behavior Scale-2, Handicap-Related Problems for Parents Inventory and Children's Assessment of Participation and Enjoyment. The Pediatric Quality of Life Inventory was completed by children and parents six months later. Results : Children with lower levels of internalising and externalising behaviours, health and social skill problems, and higher family functioning had significantly higher levels of total QOL (child and parent rated) ( r  = −.47 to −.79). In addition, children with higher levels of adaptive behaviour had significantly higher parent rated total QOL ( r  = .46). Measures of mother's stressors had moderate but not statistically significant relationships with the child's total QOL ( r  = −.31 to −.35). There were moderate and statistically significant relationships between measures of participation in physical activities and total QOL as rated by children ( r  = .42–.48) but not parents ( r  = .11–.30). Conclusions : These findings suggest potential targets to be investigated in future clinical research in rehabilitation following ABI in children to optimise QOL.